A community methodological protocol of a multisector collective impact collaboration to address older adult isolation in a rural county in the U.S. - Christine Marcos; Michael Castellano; Lindsey Skripka; Lenard W. Kaye (Frontiers in Public Health)
In 2019, a community collaborative of nearly 30 health care, social service, philanthropic, and government organizations came together to construct a community-wide plan to reduce older adult isolation in Lackawanna County, Pennsylvania. Although such collaborations have been pursued before, the current one has exceeded expectations, launched a promising pilot, and formed exciting ripple effects throughout the region's aging services landscape. Among the implementation strategies informing the initiative are the use of an interorganizational shared screening tool to identify isolation risk, a team of older adult peer navigators to provide one-on-one assistance and foster connections for those who are isolated, and a major public awareness campaign to educate residents on the negative health impacts of isolation and reduce the stigma felt by many living socially disconnected lives. This article will summarize the methodological process used in developing a cohesive, multi-sector collective impact coalition, as well as examine the limitations and future directions for this initiative.